Süd-Italien Apulien, Basilikata, Kalabrien, Kampanien - Weber, Hans; Fischer, Heinz-Joachim 1944- (DuMont, 1986)
Fotoboek.
Keywords: Kunst; Apulien; Kalabrien; Basilicata; Kampanien; Italien -- Süd; Bildband